THE GROWTH AND YIELDS OF LETTUCE (LACTUCA SATIVA L.) ON A AQUAPONIC NFT (NUTRIENT FILM TECHNIQUE) SYSTEM WITH THREE DIFFERENT TYPES OF FISH - Binawati, Diah Karunia; Puspita, Diajeng Amelia (Lux Mensana: Journal of Scientific Health, 2023)
Introduction. Lettuce Cultivation (Lactuca sativa L.) with an aquaponic system can be used as an alternative to meet the food needs of the community in the midst of reduced agricultural land. The purpose of this research is to determine the types of fish that affect the growth and yield of lettuce (Lactuca sativa L.). The types of fish used in this research were tilapia, catfish and goldfish measuring 6-8 cm with a stocking density of 20 individuals. The observation variables included number of leaves, chlorophyll and wet weight of lettuce (Lactuca sativa L.). Methods. The research data were analyzed using One Way Anova Test and Duncan Multiple Range Test (DMRT). Result and Analysis. The results showed that goldfish gave optimal results on the number of leaves and wet weight of lettuce (Lactuca sativa L.), while catfish gave optimal results on the lettuce (Lactuca sativa L.) chlorophyll. Discussion. The different types of fish have a significant effect on the number of leaves, chlorophyll content and wet weight of lettuce plants (Lactuca sativa L.). the goldfish treatment (P3) gives optimal result on the number of leaves and wet weight of lettuce plants, while catfish treatment (P2) gives optimal results on chlorophyll of lettuce plants in the NFT aquaponic system.